2016
DOI: 10.1093/mnras/stw2197
|View full text |Cite
|
Sign up to set email alerts
|

Type Ia supernovae within dense carbon- and oxygen-rich envelopes: a model for ‘Super-Chandrasekhar’ explosions?

Abstract: We investigate the consequences of fairly normal Type Ia supernovae being embedded in compact and dense envelopes of carbon and oxygen rich circumstellar material by means of detailed radiation hydrodynamic simulations. Our main focus rests on exploring the effects of the interaction between ejecta and circumstellar material on the ejecta evolution and the broad-band light curve. In our calculations, we find that a strong reverse shock efficiently decelerates and compresses the ejecta material. This leads to a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 67 publications
4
50
0
Order By: Relevance
“…Prominent examples include studying SN 1987A , supernova shock breakouts (e.g. Blinnikov & Tolstov 2011), calculating light curves for SNe Ia (Blinnikov et al 2006;Woosley et al 2007), exploring super-luminous supernovae (Baklanov et al 2015;Sorokina et al 2016), investigating pair-instability supernovae (Kozyreva et al 2017) or studying ejecta-CSM interaction in the context of super-Chandrasekhar SNe Ia (Noebauer et al 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Prominent examples include studying SN 1987A , supernova shock breakouts (e.g. Blinnikov & Tolstov 2011), calculating light curves for SNe Ia (Blinnikov et al 2006;Woosley et al 2007), exploring super-luminous supernovae (Baklanov et al 2015;Sorokina et al 2016), investigating pair-instability supernovae (Kozyreva et al 2017) or studying ejecta-CSM interaction in the context of super-Chandrasekhar SNe Ia (Noebauer et al 2016).…”
Section: Methodsmentioning
confidence: 99%
“…In this work, we employ the parameterized framework of spherical envelope models (Hoeflich & Khokhlov 1996) and make use of the observed spectral evolution and photometric properties of ASASSN-15hy to constrain model parameters. This class of models has been previously shown to provide a consistent picture for the 03fg-like object LSQ14fmg (Hsiao et al 2020) and the observed slow rise and decline of SN 2009dc (Noebauer et al 2016). The envelope models may be consistent with the core degenerate (CD) scenario (e.g., Kashi & Soker 2011).…”
Section: Envelope Modelsmentioning
confidence: 58%
“…ASASSN-15hy's relatively low peak luminosity and broad light curves place it into a specific, and somewhat unusual, area of parameter space. As ASASSN-15hy has a low Si velocity at maximum light, which translates into a relative large M env , previous sets of envelope models which detonate (Khokhlov et al 1993;Hoeflich & Khokhlov 1996;Quimby et al 2007) predict a higher peak luminosity than majority of other 03fglike events and generally slower rise and decline (Noebauer et al 2016). The secondary model criteria such as M defl and Z may be the keys to explain the peculiarity of ASASSN-15hy.…”
Section: Best-matching Modelmentioning
confidence: 90%
See 1 more Smart Citation
“…Fortunately, as noted above, such calculations can usually be performed as a post-processing step on the ejecta that have been dynamically simulated into the homologous phase. There are important exceptions, however, most notably for scenarios that involve ongoing dynamics as the explosion ejecta interact with a dense environment (see, e.g., Fryer et al 2010, Blinnikov and Sorokina 2010, Noebauer et al 2016.…”
Section: Radiative Transfer Considerationsmentioning
confidence: 99%